Divorcing traditions : Islamic marriage law and the making of Indian secularism - Lemons, Katherine (Cornell University Press, 2019)
"This book seeks to reshape our understanding of secularism, Muslim law, and divorce in contemporary India. Drawing on the most seminal recent analyses of secularism--including those of Hussain Ali Agrama and Saba Mahmood, as well as the longstanding work of Talal Asad--Lemons argues that secularism in the post-colonial Indian context entails not the separation of religion from the state, but rather the state's definition and regulation of religion, and hence the inevitable intertwining of religion and politics. Neither a particular disposition, nor a particular content, the secular marks instead this regulatory interest of the state (as well as of non-state actors). This insight enables Lemons to show how a variety of arenas that respond to marital strife and adjudicate divorce among Muslims--ranging from women's arbitration centers (mahila panchayats), to jurists' fatwas, to "Shari'a" courts, to muftis' ritual healing practices--are engaged in the secular work of continually defining religion and law"--